2019
DOI: 10.1186/s13018-019-1484-3
|View full text |Cite
|
Sign up to set email alerts
|

The combination of microfracture with induction of Wnt / β- Catenin pathway, leads to enhanced cartilage regeneration

Abstract: IntroductionMicrofracture does not lead to complete healing of full-thickness cartilage defects. The aim of this study was to evaluate the effect of modifying Wnt/β-catenin signaling following microfracture, on the restoration of a full-thickness cartilage defect in a rabbit model. The modification of the canonical Wnt pathway was achieved through per os administration of lithium carbonate, which is an intracellular inhibitor of glycogen synthase kinase 3-β (Gsk3-β) and therefore induces Wnt/β-catenin signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…These serum levels are slightly lower than the range of 0.6-1.2 mM/L, concentrations achieved and maintained during lithium therapy in human subjects. 26 This ostensibly low serum concentration was enough to induce chondrogenic differentiation of the bone marrow-derived MSCs accumulated inside the microfracture clot. In the case of extracellular Wnt inhibitors, a dose-dependent effect is also observed, as the higher dose of DKK1 resulted in a 30% reduction of the pre-hypertrophic population, whereas the lower amount reduced the pre-hypertrophic population by 46%.…”
Section: Orthopedic Reviewsmentioning
confidence: 96%
See 2 more Smart Citations
“…These serum levels are slightly lower than the range of 0.6-1.2 mM/L, concentrations achieved and maintained during lithium therapy in human subjects. 26 This ostensibly low serum concentration was enough to induce chondrogenic differentiation of the bone marrow-derived MSCs accumulated inside the microfracture clot. In the case of extracellular Wnt inhibitors, a dose-dependent effect is also observed, as the higher dose of DKK1 resulted in a 30% reduction of the pre-hypertrophic population, whereas the lower amount reduced the pre-hypertrophic population by 46%.…”
Section: Orthopedic Reviewsmentioning
confidence: 96%
“…The 1-week treatment group was superior to the control group in two out of six ICRS categories. 26 The aforementioned studies are summarized in Table 1.…”
Section: Enhanced Msc Chondrogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…12 These techniques include combining cells, scaffolds and growth factors, or chemical drug therapies with marrow stimulation techniques to enhance the quality of repaired cartilage. 7,14,29,37,41,45,47 Angiotensin receptors are expressed in hypertrophic cartilage and are implicated in osteoarthritis (OA) development. 58 Furthermore, it also has been shown that the angiotensin II–induced activation of transforming growth factor β1 (TGF-β1)–phosphorylated small mothers against decapentaplegic 2/3 (pSmad2/3) signaling is associated with tissue fibrosis.…”
mentioning
confidence: 99%
“…In the osteoblast experiments in this study, the results of qRT-PCR indicated that quercetin could significantly promote the upregulation of IL-1β gene expression in SANFH osteoblasts; studies also showed that IL-1β could inhibit the production of DKK1, thereby promoting the activation of Wnt signaling [59]. The activation of Wnt signaling could enhance the formation of MSC cartilage [60][61][62]. Therefore, it suggests that quercetin in this study may activate the Wnt signaling pathway by upregulating IL-1β gene expression in osteoblasts and finally promote cartilage formation.…”
Section: Discussionmentioning
confidence: 99%